The Efficiency of κ-Carrageenan-Chitosan-PVA-MWCNTs Membranes in Removing Methylene Blue, Rhodamine B, Bromocresol Purple, and Murexid from Water - Widarti, Sri; Suprianti, Yanti; Kurniasetiawati, Annisa Syafitri; Tritjahjono, Rachmad Imbang (ASEAN Journal of Chemical Engineering, 2023)
The electrocoagulation method has been proven to be highly effective in removing metal ions from water, with a removal efficiency of over 97%. However, in terms of removing organic pollutants such as synthetic dyes, the efficiency of electrocoagulation is still relatively low. A hybrid approach combining electrocoagulation with membrane filtration has been proposed to enhance the removal of organic contaminants. Eco-friendly membranes made from renewable natural polymers like carrageenan and chitosan, reinforced with synthetic polymers such as polyvinyl alcohol and carbon nanotubes, have shown to be promising for this application. In this study, membranes with varying chitosan/carrageenan ratios of 0.2, 0.33, 0.5, and 0.71 (g/g) were used to remove synthetic dyes, including methylene blue, rhodamine B, bromocresol purple, and murexid, at a concentration of 200 ppm from 8.5 ml of water. From the SEM images, the four membranes have almost the same surface and cross-section morphology. The results showed that the membrane with a chitosan/carrageenan ratio of 0.71 exhibited the highest removal efficiency for all synthetic dyes. The parameter affecting the membrane’s removal efficiency is the interaction between the membrane and synthetic dyes. Murexid, an anionic dye, achieved a 100% removal efficiency, surpassing cationic dyes such as rhodamine B and methylene blue. Besides interactions, the dye’s molecular size determines the removal’s efficiency. The molecular size of rhodamine B is larger than that of methylene blue, and the removal efficiency of rhodamine B (98.4%) is greater than methylene blue (91%). Bromocresol purple is almost the same size as rhodamine B but not ionic because it has the lowest removal efficiency of 34.55%.